From “doing alone” to “working together”—Research on the influence of spiritual leadership on employee morale - Jiang, Juan; Ye, Zhixiao; Liu, Jing; Shah, Wasi Ul Hassan; Shafait, Zahid (Frontiers in Psychology, 2023)
Spiritual leadership is a beneficial attempt to implement organizational strategy and sustainable development by improving employees’ personal spiritual needs, stimulating employees’ intrinsic motivation, sense of responsibility, and calling in the work process. We theoretically illustrate that spiritual leadership has a significant positive impact on employee morale. The factors of personal self-efficacy and interpersonal trust play an intermediary chain role in this process. SPSS 24.0 and Process3.5 were used to test the mediating effect using multilevel regression analysis and the bootstrap method. Survey data collected from 278 employees from Chinese organizations supported our proposed hypotheses. The research verifies it is necessary to pay attention to improving the spiritual needs of leaders and employees in organizational development. Through the cultivation, spiritual leadership not only can stimulate the cohesion of the organization and the intrinsic motivation of the employees, but also is of great significance to enrich the spiritual life of the organization members.